News with a View : essays on the eclipse of objectivity in modern journalism - St. John, Burton, 1957-; Johnson, Kirsten A., 1974- (Jefferson, N.C. : McFarland, 2012)
"This volume offers new examinations of how the traditional notion of objectivity is changing as professional journalists grapple with a rapidly evolving news terrain--one that has become increasingly crowded by those with no journalistic credentials"--Provided by publisher.
Introduction: challenges for journalism in a post-objective age / Burton St. John III and Kirsten A. Johnson -- Historical perspectives. "Gagged, mincing neutrality": Horace Greeley on advocacy journalism in the early years of the penny press / Daxton R. "Chip" Stewart -- The pride and reward of falisfication: post-objectivity as post-responsibility / Aaron Barlow -- A new model of objectivity: investigative reporting in the twentieth century / Gerry Lanosga -- Contemporary examinations, conversational journalism and journalist-audience relations: new rules, new voices / Doreen Marchionni -- The sociality of news sociology: examining user participation and news selection practices in social media news sites / Sharon Meraz -- Why contribute? motivations and role conceptions among citizen journalists / Deborah S. Chung and Seungahn Nah -- Morality, the news media, and the public: an examination -- Of comment forums on U.S. daily newspaper websites / Serena Carpenter and Robin Blom -- Global considerations. Post-objectivity and regional Russian journalism / Wilson Lowrey and Elina Erzikova -- Journalism from the perspective of "we": how group membership shapes the role of the community journalist / John A. Hatcher -- Engagement as an emerging norm in international news agency work / John Jirik -- Objectivity and theory. Why objectivity is impossible in networked journalism and what this means for the future of news / David Michael Ryfe -- Disrespecting the doxa: The daily show critique of CNN's struggle to balance detachment and connectedness / Burton St. John III -- Gatekeeping in the digital age: a new model for a post-objective world / Kirsten A. Johnson -- Contemporary news production and consumption: implications for selective exposure, group polarization, and credibility / Ethan Hartsell, Miriam J. Metzger and Andrew Flanagin.
Includes bibliographical references and index.
Keywords: Journalism -- Objectivity